(untitled) (Research Journal Tahqeeqat, 2025)
In this study, the ghazal of Tauseef Tabassum- an eminent poet associated with the postmodern era who emerged during the 1990s- has been examined in the context of scientific knowledge. His ghazal, through its symbolic and metaphorical semantic system, offers new dimensions to knowledge and art. Science is an empirical discipline that considers reality to be measurable, observable, and verificat ion. The Scientific trend of the nineteenth century influenced global intellectual attitudes and declared scientific authority as the sole path to truth. However, the atomic devastation brought about by science divided its worth into two domains: the epistemic and the experimental. From an intellectual and theoretical standpoint, Foucault’s concept of discourse introduces new perspectives for understanding scientific knowledge. Drawing upon these scholarly debates, this study presents a semantic interpretation and explanation of scientific concepts through the ghazal “Asman The-e-Ab”.